Non-Intrusive Item Authentication with High Robustness for RFID-Enabled Logistics - Xue, Jiawei; Duan, Chunhui; Li, Fan; Feng, Qihua; Wang, Ziang; Zhu, Yinan (Annual Joint Conference of the IEEE Computer and Communications Societies, 2025)
RFID technology has found extensive applications in the realm of smart logistics, facilitating rapid package sorting and tracking. Harnessing the potential of RFID in addressing concerns related to logistics security holds significant promise and meaning. Past efforts either focused solely on the status of tags or package boxes, or interfered with the normal logistics processes. To detect the status of goods inside the packages and provide timely alerts for instances of loss, replacement, or damage, we propose RF-Express, a non-intrusive and anti-interference item authentication method. RF-Express enables seamless authentication of items during the logistics process, utilizing the pervasive RFIDs with almost no additional costs. Specifically, by tactfully arranging a pair of tags on each package and extracting representative features from the backscatter signals of the tags, we manage to discern the authenticity of the item with high precision across various multipath environments. Besides, a feature matching algorithm based on the triplet network is employed to further reinforce the robustness of the system. We implemented the RF -Express prototype on commercial devices and conducted plenty of experiments. It is demonstrated that RF-Express achieves a true acceptance rate of 90.97% and a true rejection rate of 94.38% on average under common attack scenarios.